Comparative Study between Optical and Ultrasonic Measurement of Axial Length and Anterior Chamber Depth in Normal, Long and Short Eyes - Rashid, Harunur; Sharif, AQM Omar; Shipu, Zinat Rehana; Ghosh, Debashish; Akhter, Sofia; Priyadarshini, Faizah; Sharmee, Tania Hossain (Journal of Shaheed Suhrawardy Medical College, 2020)
Purpose: The aim of the study is to evaluate and analyze the difference between optical and ultrasonic measurement regarding axial length (AL) and anterior chamber depth (ACD) in normal, long and shorts eyes. Methods: A prospective study conducted on 145 patients enrolled for cataract surgery. Total 145 eyes have been tested. The eyes were divided into three groups depending on their AL; normal eye (22mm – 25mm), long eye (>25mm) and short eye (< 22mm) groups. The eyes have been measured by both Swept Source Optical biometry and Applanation Ultrasoundbiometry. Results: Statistical analysis of the sub groups showed, mean axial length was 23.68mm and 23.59mm by optical and applanation biometry with standard deviation of 2.34mm and 2.30mm. The mean of anterior chamber depth was 3.14mm by optical and 3.12mm by ultrasonic method with standard deviation of 0.48mm and 0.44mm. The sample size was 145. The correlation statistics between the methods was 0.995 and 0.934 with mean difference of 0.08 and 0.02 for AL and ACD respectively. The eyes were divided into normal eye (22mm-25mm), long eye (>25mm) and short eye (<22mm) groups according to the measurement of axial length. There was no statistically significant difference in axial length and anterior chamber depth measurement by optical method (P=0.52) and ultrasonic method (P= 0.17). So, it can be said that, there is good agreement between the two methods regarding measurement. Conclusion: There is no significant difference in measurement of axial length and anterior chamber depth by optical and ultrasonic method of biometry. J Shaheed Suhrawardy Med Coll, December 2019, Vol.11(2); 147-154